Octagon Modelling Using Parallel Projection of Optical Tomography - Naizatul Shima Mohd Fadzil; Ruzairi Abdul Rahim; Juliza Jamaludin; Siti Zarina Mohd Muji; Mohd Fadzli Abdul Sahib; Mohd Saiful Badri Mansor; Nor Muzakkir Nor Ayob; Mohd Fahajumi Jumaah; Suzanna Ridzuan Aw; Mohd Zikrillah Zawahir (Penerbit UTM Press, 2024)
Volume :70 No: 3 : Special Issue on Advanced Sensors and Instrumentation Systems